SCIENTIFIC LANGUAGE CULTURE OF THE FUTURE MASTER AS A COMPONENT OF HIS PROFESSIONAL COMPETENCE - Bilavych, Halyna; Savchuk, Borys; Ilnytsky, Vasyl; Fedchyshyn, Nadiya (Mountain School of Ukrainian Carpaty, 2020)
The article is devoted to the problem of formation of scientific language culture (ecology) of the future masters. The authors define the culture (ecology) of the Ukrainian scientific language as the perfect level of knowledge of scientific language of the future masters, in particular the norms of the Ukrainian literary language, scientific style, and its varieties. The study results showed that the level of scientific language (both oral and written) of the future masters is mostly average and low. The material for the study was the scientific texts of undergraduates: master's theses, articles, scientific reports, etc. (total 210 units). We analyzed them to identify linguistic and stylistic errors. We also conducted a survey (oral and written) of the future masters, the purpose of which was to identify the state of mastery of scientific Ukrainian language. According to the respondents, usually the majority of teachers (57%) does not pay attention to the language side of scientific work. 43% of undergraduates said that their supervisors pointed out errors in the text of the work and encouraged them to edit the scientific text. The article analyzes typical errors in students’ scientific texts, indicates their causes and outlines ways to eliminate them. It was found that most mistakes in master's theses and scientific articles of students occur when choosing the right terms; students often do not know how to use them properly, nor correctly translate into Ukrainian a term from Russian or English. There is a need to edit a scientific text. The large percentage of errors (94%) is due to the influence of the Russian language, which is constantly experienced by the Ukrainian scientific language. We also asked undergraduates whether they had enough of the knowledge they received at the university to write a master's thesis. 76% of respondents emphasized that in the course of studying the discipline "Fundamentals of Scientific Research" teachers usually "did not pay much attention" to the linguistic and stylistic editing of a scientific text. In our opinion, it would be expedient to teach this subject to a philologist who would emphasize to students the norms of the Ukrainian scientific language. It is also worth offering undergraduates an elective course on the basics of scientific text editing. These and other measures would contribute to the formation of scientific language culture of the future masters.